Cancer-associated SF3B1 mutations affect alternative splicing by promoting alternative branchpoint usage - Alsafadi, Samar; Houy, Alexandre; Battistella, Aude; Popova, Tatiana; Wassef, Michel; Henry, Emilie; Tirode, Franck; Constantinou, Angelos; Piperno-Neumann, Sophie; Roman-Roman, Sergio; Dutertre, Martin; Stern, Marc-Henri (Nature communications, 2016)
Hotspot mutations in the spliceosome gene SF3B1 are reported in ∼20% of uveal melanomas. SF3B1 is involved in 3′-splice site (3′ss) recognition during RNA splicing; however, the molecular mechanisms of its mutation have remained unclear. Here we show, using RNA-Seq analyses of uveal melanoma, that the SF3B1 R625/K666 mutation results in deregulated splicing at a subset of junctions, mostly by the use of alternative 3′ss. Modelling the differential junctions in SF3B1 WT and SF3B1 R625/K666 cell lines demonstrates that the deregulated splice pattern strictly depends on SF3B1 status and on the 3’ss-sequence context. SF3B1 WT knockdown or overexpression do not reproduce the SF3B1 R625/K666 splice pattern, qualifying SF3B1 R625/K666 as change-of-function mutants. Mutagenesis of predicted branchpoints reveals that the SF3B1 R625/K666 -promoted splice pattern is a direct result of alternative branchpoint usage. Altogether, this study provides a better understanding of the mechanisms underlying splicing alterations induced by mutant SF3B1 in cancer, and reveals a role for alternative branchpoints in disease. Mutations in the splicing factor SF3B1 are found in uveal melanoma. Here, Alsafadi et al . use RNA-sequencing data from these cancers and experimental models, and show that mutant SF3B1 promotes alternative branchpoints in a specific gene subset and that the mutant protein gains a new function.